The report of Chief of the General Staff of USSR marshal Alexander Jegorov about his visit in Lithuania, Latvia, and Estonia on 15th-26th of February, 1937 - Butkus, Zenonas; llmjarv, Magnus (Lietuvos istorijos studijos, 2008)
A. Jegorov’s report to the People’s Commissar of Defence Kliment Voroshilov that is being published has been found in the Russian State Military Archive (F. 33987. Ap. 3. B. 1035. L. 118-147). This report is a unique testimony of the USSR policy and international relations and a sign of the activity of the policy in question that in principle has never been used in scientific research. It raises doubts about the statement that has been and is still widely used in the works devoted to history, namely, that parceling out of the Baltic states in 1939 and their occupation in 1940 have been the actions provoked by the intricacies in the international situation and may not be directly associated with the preceding Soviet policy, which in general failed to be conceptual and well-planned and that at that time they received the given states not as a result of "their Baltic policy" but directly from "the hands of Berlin." Commenting on the goals of A. Jegorov’s visit to the Baltic states in 1937, it may be simply stated that it was a formal reciprocal visit since nearly a year ago heads of the headquarters of the armed forces of Lithuania, Latvia, and Estonia Jonas Čemius, Martinš Hartmanis, and Nikolaj Rek visited Moscow to participate in the festivities of May 1 of 1936. The visit, however, also pursued certain propaganda goals; there was a striving to demonstrate the growing power of the Soviet State and especially that of the Red Army as well as a wish to demonstrate the concern about the security of not only their own country but also that of the neighbouring countries. Besides, the authors of the publication make an assumption that sending A. Jegorov to the Baltic States, Stalin wanted, first and foremost, to instigate Berlin’s interest in Moscow and make it resume the slackening relations. The fact that the Soviet policy was supervised by the only person - Stalin - and the hasty preparation of the visit without prior decision whether it had to be a visit only to Lithuania or to all three Baltic States makes it necessary to analyze it within the broader context of international relations. Leaders of the USSR wanted to demonstrate to Germany the existence of the two options of the development of mutual relations - concord or confrontation. The notorious David Kandelaki mission pointed to concord while A. Jegorov’s visit pointed to confrontation and mutual competition. The visit had to bring it home to Hitler that the USSR could develop and consolidate its influence at the borders of Germany - Baltic States - or even form a military alliance with them. Hitler, however, rejected the hand of Moscow that was making a reach, assuming that it was no more than a manoeuvre of the Soviets and that their approximation with Germany was only aimed at exercising a certain pressure on France to make it more willing to form a real military alliance, which could also be acceded by England. In this way, Nazi Germany might have been enclosed. The visit aimed at ascertaining what the influence of Germany in the Baltic States was and at the same time to show that the Soviets had a stronger position in the given states, which could even be further consolidated or even a military alliance with them was feasible. The visit has to be associated with the confrontation of Moscow and Berlin, with their struggle for influence in the Baltic States and Stalin’s attempts to transform that confrontation into an agreement, which he managed to reach in August of 1939. In the course of the visit, high-ranking Soviet military servicemen had a possibility to eyewitness the military, political, and economic situation of the Baltic States, which could let them make a strategic assessment of the given region. The report stated that politicians and military servicemen of the Baltic States, with few exceptions, were oriented to the USSR and that those states had no plans to oppose the possible Soviet expansion, which meant that the road in that direction was not blocked. Paying that visit as a demonstration of support to Lithuania, the Soviets dodged any concrete obligations to assist it in its struggle against Poland or regain Vilnius. The issue of the military cooperation between the Baltic States and the USSR was never debated. The Soviets refused to sell arms not only to Lithuania but also to Latvia and Estonia. Although the opinion that the visit demonstrated a much closer military relationship with Lithuania than that with Latvia and Estonia was widely spread, the published report fails to confirm it. A. Jegorov’s assessment of the Lithuanian armed forces was more critical and less favourable than that of its both Northern neighbours. The published source supplements and adjusts the existing data related to the relations between the Baltic States and the USSR.